Antimicrobial studies of the Zn(II) complex of S-benzyl-β-(N-2-methyl-3-phenylallylidene)dithiocarbazate. Issue 7 (18th April 2022) - Bhat, Rayees A.; Singh, Kaman; Kumar, D.; Kumar, Ashok; Mishra, Prashant
Abstract: Antimicrobial resistance is a global concern with increases in multidrug-resistant bacteria. New coordination compounds could offer a solution. We report S-benzyl- β -(N-2-methyl-3-phenylallylidene)dithiocarbazate (HL) forming bis[S-benzyl- β -(N-2-methyl-3-phenylallylidene)dithiocarbazate]zinc(II), [Zn(L)2 ]; its bio-efficacy has been examined against the growth of gram-positive Staphylococcus aureus and gram-negative Escherichia coli to evaluate antimicrobial potential. The inhibition diameter results of E. coli and S. aureus were compared to standard drug (Erythromycin). Characterization by UV–vis, FT-IR, Raman, 1 H NMR, 13 C NMR, and mass spectroscopy revealed that [Zn(L)2 ] has distorted square planar geometry, coordinated through Nimine and Sthiolate . Density functional calculations of [Zn(L)2 ] in gas phase were performed by DFT (RB3LYP) with LanL2DZ basis set and the results are: chemical hardness (ɳ) 0.007915 eV, chemical potential (µ) 0.11643 eV, electron affinity (A) −0.10852 eV, softness (S) 7.855 eV, ionization energy (I) −0.12435 eV, electronegativity (χ) −0.11643 eV, dipole moment (D) 4.0690 Debye and with stabilization energy of −1718.1753 eV. Vibrational energy distribution analysis (VEDA)-4 software was employed for theoretical FT-IR spectrum, which yielded 237 fundamental vibrational modes. Theoretically calculated parameters like UV–vis, FT-IR, 1 H NMR, 13 C NMR, Raman, HOMO–LUMO energy gap and electrostatic potential were in conformity with experimental observations. The compound was docked with different receptors 1HT0, 1U3T, 1U3V, and 3S7S to find the best ligand–protein interactions. Graphical Abstract: UF0001